Inhibitory effect of Streptococcus salivarius K12 and M18 on halitosis in vitro - Hyun‐Jun Yoo; Su‐Kyung Jwa; Da‐Hui Kim; Yun‐Jeong Ji (Wiley, 2020)
Abstract Background The aim of the study was to observe the antimicrobial activity of Porphyromonas gingivalis and Treponema denticola as well as the effect on reducing volatile sulfur compounds (VSCs). Materials and methods After P. gingivalis and T. denticola were cultured with or without Streptococcus salivarius K12 and M18, VSCs were measured by Oral Chroma. In order to analyze the mechanism for malodor control, the antimicrobial activity of S. salivarius K12 and M18 against P. gingivalis and T. denticola was assessed. SPSS 21.0 was used for data analysis with the Kruskal-Wallis and Jonckheere-Terpstra tests. Mann-Whitney test was applied for post hoc analysis. Results P. gingivalis and T. denticola VSC levels were reduced by high concentrations of S. salivarius K12 and M18 during coculture. The concentrations were lower than those of single culture (p < .05). An antimicrobial effect was detected on P. gingivalis, and T. denticola by 50% S. salivarius K12 and M18. The spent culture medium and whole bacteria of S. salivarius K12 and M18 reduced the levels of VSCs below the amount in a single culture of P. gingivalis and T. denticola (p < .05). Conclusion S. salivarius K12 and M18 decreased the levels of VSCs originating from P. gingivalis and T. denticola.